(untitled) (Academicia Globe: Inderscience Research, 2021)
The article deals with the norms that exists in the Russian written language. Having well established norms of writing,spelling punctuation,written speech remains understandable after decades and even hundreds of years . However, being a reflection of oral speech,responding to the trends of time,written speech inevitably undergoes changes.